FREQUENCY OF CONGENITAL ANOMALIES OF THE KIDNEY AND URINARY TRACT BY MEANS OF ULTRASONOGRAPHY IN NEONATES AT A TERTIARY-CARE HOSPITAL - Rasool, Uzma; Rehman, Saqib Ur; Ayaz, Saeed Bin; Tariq, Ghulam Rasool; Shah, Ghulam Ghaus (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of congenital anomalies of the kidney and urinary tract by means of ultrasound in neonates.Study Design: Cross-sectional study.Place and Duration of Study: Department of Radiology and Diagnostic Imaging, Rehman Medical Institute, Peshawar, from May 2015 to Jan 2016.Methodology: A total of 150 neonates reporting for routine abdominal ultrasonography were included. Honda Convex Scanner model HS-2000 with probe of frequency of 5-7 MHz was used for the ultrasonography.Results: Mean age of the neonates was 13.8 ± 7.5 days. Seventy-six (50.7%) were male and 74 (49.3%) were female. Congenital anomalies of the kidney and urinary tract were observed in 10 (6.7%) neonates. Most neonates had more than one anomaly. The left side was involved in 6 (4%) neonates while right side was involved in 4 (2.7%). Hydronephrosis was the most common abnormality found in 8 (5.3%) cases. The location of kidneys was abnormal (ectopic) in 2 (1.3%) neonates. Abnormal dimension was seen in seven cases and abnormal corticomedullary differentiation was found in 5 (3.3%) cases. Non-symmetrical cases were 5 (3.3%). Hydroureter was observed in 3 (2%) neonates and urinary bladder was abnormal in 2 (1.3%) neonates.Conclusion: The frequency of congenital anomalies of the kidney and urinary tract in neonates by means of postnatal ultrasonographic scan in our study population was 6.7%. Hydronephrosis was the most common anomaly.